Le développement de la viticulture antique dans le bassin versant de la Loire à l’époque romaine (Gaule centrale) et la question de la vigne biturica - Alain Ferdière (Revue Archéologique du Centre de la France)
The development of viticulture through Gaul, whose economic and cultural importance is well known, is a well-documented question today, including for inland Gaul. However, this has not been treated on the scale of the vast territory of central Gaul (Galliae Lugdunensis and Aquitania) represented by the entire Loire watershed. This is what we propose to examine here in detail – from the origins to the 6th-7th centuries – for this set of cities concerned, scrutinized one by one, by mobilizing all the documentation through, in turn, textual, iconographic and archaeological data of all kinds, from the facilities assigned to this production to archaeo-botanical data, whose relative heuristic value will be weighed. This will allow us to review, in a historiographical and critical way, the abundant file of the biturica vine, by examining the data of the city of Bituriges Vivisci in parallel with those of Bituriges Cubi.